Pendidikan Karakter Melalui Mata Pelajaran Pengembangan Diri dan Budaya Sekolah Berbasis Keislaman - Henni Yusda Rahmiyanti (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2017)
Research on Culture and Character Education is a mind that is practical and can be implemented in an atmosphere of education in schools at the present time. Nevertheless, the implementation of the Education Culture and Character require changes in the implementation of the educational process that occurs in the school at the present time. The necessary changes do not change the applicable curriculum but require a new attitude and new skills of teachers, principals and school counselors. Attitudes and new skills is a requirement that must be met (conditio sine qua non) for the successful implementation of Culture and Character Education. Changes in attitude and mastery of the skills required can only be developed through education in-service focused, sustained, and systemic.